Stability criteria for 4H-SiC bulk growth - Straubinger, Thomas; Bickermann, Matthias; Hofmann, Heinz-Dieter; Weingärtner, Roland; Wellmann, Peter; Winnacker, Albrecht (Materials Science Forum, 2001)
Types i and ii of polytype instabilities (6H/15R) were observed to be not stable and overgrown by 4H. Furthermore type i could be avoided by a seeding procedure with low supersaturation. No dependence on pressure or axial temperature gradient was noticed for the type ii polytype generation mechanism. Concerning the complete conversion to 6H, 4H stability showed no correlation with the argon pressure but we found a critical temperature for conversion, which depends on the axial temperature gradient. Far low axial T-gradients the critical temperature decrease
Keywords: 4H-SiC; Polytype; PVT